Artificial neural network (ann) approach to prediction of diffusion bonding behavior (shear strength) of ni-ti alloys manufactured by powder metalurgy method - Taskin, Mustafa; Dikbas, Halil; Caligulu, Ugur (Association for Scientific Research, 2008)
In this study, Artificial Neural Network approach to prediction of diffusion bonding behavior of Ni-Ti alloys, manufactured by powder metallurgy process, were obtained using a back-propagation neural network that uses gradient descent learning algorithm. Ni-Ti composite manufactured with a chemical composition of 51 % Ni - 49 % Ti in weight percent as mixture with a average dimension of 45?m. Diffusion welding process have been made under argon atmosphere, with a constant load of 5 MPa, under the temperature of 850, 875, 900 and 925°C and, in 20, 40 and 60 minutes experiment time. Microstructure examination at bond interface were investigated by optical microscopy, SEM and EDS analysis. Specimens were tested for shear strength and metallographic evaluations. After the completion of experimental process and relevant test, to prepare the training and test (checking) set of the network, results were recorded in a file on a computer. In neural networks training module, different temperatures and welding periods were used as input, shear strength of bonded specimens at interface were used as outputs. Then, the neural network was trained using the prepared training set (also known as learning set). At the end of the training process, the test data were used to check the system accuracy. As a result the neural network was found successful in the prediction of diffusion bonding shear strength and behavior. © Association for Scientific Research.
Keywords: ANN; Diffusion Bonding; Ni-Ti; Powder Metallurgy; Shear Strength